1, 4‐Diketones from Cross‐Conjugated Dienones: Potassium Permanganate‐Interrupted Nazarov Reaction1. (3rd July 2015) - Kwon, Yonghoon; Schatz, Devon J.; West, Frederick G.
Abstract A domino potassium permanganate‐interrupted Nazarov reaction to yield syn‐2, 3‐disubstituted 1, 4‐diketones via a decarbonylative cleavage of the Nazarov oxyallyl intermediate, believed to be without precedent, is presented. This process allows syn substituents to be established stereospecifically on the 2‐carbon bridge connecting the ketone carbonyl carbons, and the formation of one carbon–carbon and two carbon–oxygen bonds. Two carbon–carbon bonds are cleaved in this process.